Effect of Heating Power on The Synthesis of Titanium Dioxide Particles by Direct Heating Method for Photodegradation of Methylene Blue Solution - Koe, Chee Meng; Ng, Guan Sheng; Pung, Swee-Yong (International Journal of Integrated Engineering, 2024)
Dyes are extensively used in the textile industry. Untreated dye-containing wastewater is hazardous to humans and the environment. Advanced oxidation processes (AOPs) based on heterogeneous TiO2 photocatalyst is a technology that has been proven successful for effluent treatment. Nevertheless, use of TiO2 photocatalyst in particles form could result in loss of TiO2 photocatalyst over time during effluent treatment. Immobilization of TiO2 photocatalyst on substrates could address this problem. In this study, a method called direct heating (DH) was devised to deposit TiO2 particles on kanthal wires to prevent the particles from being washed away during effluent treatment. This method has low equipment cost and short synthesis duration when compared to others. The TiO2 particles synthesized at 50 W in 15 min gave the best photodegradation efficiency, which was 36.3 % under 90 mins of UV light irradiation. It contained a mixture of anatase (22.5 %) and brookite (77.5 %), with an average particle size of 139.34 ± 15.89 nm. The TiO2 particles had high surface coverage on kanthal wire with little agglomeration. The current work presents a captivating and low-cost setup, providing easy control over synthesis conditions and scaling potential for immobilizing TiO2 particles on the kanthal wires.